2010
DOI: 10.1177/1475921710365415
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Guided Waves for Monitoring Chloride Corrosion in Reinforcing Bars in Concrete

Abstract: Corrosion of reinforcing steel in concrete is one of the major durability problems faced by civil engineers as they maintain an aging infrastructure. The problem accelerates since steel is embedded inside concrete. If it remains unnoticed inside concrete, it further accelerates and can cause loss of life and property. This article discusses a nonintrusive corrosion monitoring technique for early detection of damages in steel embedded in concrete. Corrosion manifests itself in debond and pitting steel bars. Gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 13 publications
3
53
0
2
Order By: Relevance
“…The authors have reported that specific ultrasonic guided wave modes are effective in monitoring core and surface areas of waveguides [32]. By studying the modal displacement and energy distribution functions, specific modes can be identified that are sensitive to surface changes [33,34]. The authors used signals from specific modes to identify different types of corrosion of steel bars and correlate them with parameters such as mass loss, residual strength and pull out strength [33].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors have reported that specific ultrasonic guided wave modes are effective in monitoring core and surface areas of waveguides [32]. By studying the modal displacement and energy distribution functions, specific modes can be identified that are sensitive to surface changes [33,34]. The authors used signals from specific modes to identify different types of corrosion of steel bars and correlate them with parameters such as mass loss, residual strength and pull out strength [33].…”
Section: Introductionmentioning
confidence: 98%
“…By studying the modal displacement and energy distribution functions, specific modes can be identified that are sensitive to surface changes [33,34]. The authors used signals from specific modes to identify different types of corrosion of steel bars and correlate them with parameters such as mass loss, residual strength and pull out strength [33]. In this investigation, the modal excitation technique is applied to monitor the development of bond between steel and concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring changes in the electrical characteristics of corroded reinforcements is one of the non-destructive monitoring methods [9][10][11][12]. The electrical conductivity and impedance of steel is changed by corrosion, and by measuring these electrical characteristics, the corrosion of the reinforcement can be monitored [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This product is the result of efforts of the South West Research Institute in Texas. Sharma and Mukherjee (2010) describe accelerated corrosion testing of rods and using guided waves tuned for high cross-sectional sensitivity. For chloride-type defects with caustic pitting and surface distortion, the decrease in surface profile sensitivity increases the sensitivity to local bar topography (Sharma and Mukherjee 2010).…”
Section: Defect Detectionmentioning
confidence: 99%